Implementation of “health promoting educational institute” strategies in the state of Himachal Pradesh, India: challenges, opportunities and the way forward - Chauhan, Gopal; Thakur, Vishal (International Journal Of Community Medicine And Public Health, 2022)
Health promotion is the process of enabling people to increase control over, and to improve their health. Schools and other educational institutes can play a vital role in inculcating health promoting behaviour at early stage of life for sustainable health and well-being. A health promoting school is one that constantly strengthens its capacity as a healthy setting for living, learning and working through multi stakeholder engagements. Health Department has a key role in developing strategies and building partnerships for health promotion at school level. Keeping in view these facts, the department of health and education developed the protocol and implementation plan for certification of educational institute as “health promoting educational institute” in the state of Himachal Pradesh in northern India. The World Health Organization (WHO) protocol for health promoting schools (HPS) has been adopted with some state specific modifications which came into force from 6th November 2020 through a notification by the state government. However, the process of certification got delayed due to the COVID pandemic and closure of the schools. The institutional ethics committee (IEC) activities and capacity building measures were strengthened and Government Senior Secondary School Mahunag in district Mandi with strength of 120 students from 6-12th class was certified as the first health promoting educational institute in the state on 18th December 2021. The purpose of this study is to discuss the process for certification of health promoting educational institute in the state of Himachal Pradesh so that the strategy can be replicated in similar settings.